THE ROLE OF PROFESSIONAL CONDUCT IN BUILDING A PEDAGOGICAL IMAGE - Firuza Narzikulova Boturovna (INTEGRATION OF SCIENCE, EDUCATION AND PRACTICE. SCIENTIFIC-METHODICAL JOURNAL, 2021)
The article considers the main idea of the role of professional behavior of a teacher in the formation of the pedagogical image. The article presents the analysis and modern concept of such definition as pedagogical and professional deontology. Pedagogical thinking and consciousness, as well as the creative potential of the teacher, which is a set of global cultural and historical experience, are considered.